PERFORMANCE OF AC-BC MIXTURE WITH ACRYLONITRILE BUTADIENE STYRENE (ABS) PLASTIC ADDITIONAL ASSESSMENT FROM MARSHALL'S PARAMETERS - Pranoto, Rizal Prasetyo (BANGUNAN, 2022)
Abstract: The problem that is often encountered in Indonesia is road damage, especially on roads with heavy traffic volume. On the other hand, Indonesia is a country that is included in the largest producer of plastic waste in the world. Efforts are needed to reduce plastic waste and to improve the quality and performance of the pavement layer, then asphalt modification with plastic added materials can be a solution. Therefore, this research uses ABS plastic waste added material to reduce waste. The purpose of this research is to describe the characteristics of the constituent materials in the AC-BC mixture with the addition of ABS, describe the effect of pavement on the AC-BC mixture using ABS added material in terms of Marshall parameters, describe the performance Residual Strength Index (IKS) on AC-BC asphalt mixture using ABS added material. The research design includes the stages of material preparation in the form of aggregate, asphalt, filler, ABS added material. Then make the test object using asphalt content of 5%, 5.5%, 6%, 6.5%,7%, and the Marshall test is carried out to obtain the Optimum Asphalt Content (KAO). Second, make KAO test objects with ABS at levels of 0%, 1.5%, 3%, 4.5%, and 6% by wet method and tested by Marshall to get KABSO (Optimum Acrylonitrile Butadiene Styrene Levels). Then, make the KAO test object with the addition of ABS to get the IKS value by immersing it for 30 minutes and 24 hours. The results obtained made KAO specimens with ABS at levels of 0%, 1.5%, 3%, 4.5%, and 6% by wet method and tested by Marshall to get KABSO (Optimum Acrylonitrile Butadiene Styrene Levels). Then, make the KAO test object with the addition of ABS to get the IKS value by immersing it for 30 minutes and 24 hours. The results obtained made KAO specimens with ABS at levels of 0%, 1.5%, 3%, 4.5%, and 6% by wet method and tested by Marshall to get KABSO (Optimum Acrylonitrile Butadiene Styrene Levels). Then, make the KAO test object with the addition of ABS to get the IKS value by immersing it for 30 minutes and 24 hours. The results obtainedthe constituent materials of AC-BC have met the 2018 Bina Marga specifications and obtained an KAO of 6.5%.The addition of ABS in the asphalt makes the mixture harder, which is indicated by a decrease in the value of penetration and ductility and an increase in the softening point of the asphalt. In addition, the addition of ABS in asphalt makes the flash point value and asphalt burn decrease.Marshall AC-BC performance with ABS obtained stability values, MQ, and VFA increased, then flow, VIM, and VMA values decreased. The optimum ABS content was obtained at 3%, the IKS value in the AC-BC mixture with the addition of ABS obtained the highest IKS value at the addition of 4.5% ABS.Keywords: acrylonitrile butadiene styrene, ac-bc, marshall parameters